Microwave sensor for defected fruit classification - Leekul, P.; Chivapreecha, S.; Krairiksh, M. (My University, 2016)
This paper presents a microwave sensor operating at the frequency of 2.45 GHz that can detect defected fruits. In this work, orange is used as an example. Granulation of orange is detected by measuring mean and standard deviation of the magnitudes of S-parameters of the orange at different positions. From the simulated S-parameters of patch antennas surrounding the fruits, it was found that the reflected signal from the fruit and the coupled signal to the antenna oriented perpendicular to the fruits provide the obvious variation and can be used as indicators for justification. This cost effective sensor is a good candidate for fruit classification.
Keywords: granulation; microwave sensor; oranges; patch antenna